Sources of solar energy as factors of sustainable development - Bošković Jelena; Đurić Katarina; Turanjanin Dragan (Ekonomija: teorija i praksa, 2017)
The focus of this paper is solar energy as one of the renewable energy sources. When viewed historically, our society has always had a problem with the consequences of irrational use of resources left behind. For this reason, and at this stage of civilization development, renewable energy sources need to be widely used, because the reserves of non-renewable sources are being exploited greatly, while the level of pollution is reaching a critical point. Renewable sources are not new, their use was recorded even at the earliest stages of the development of human society, and this was mostly related to the use of solar energy. The today's modern technology and development allow for the multiple use of solar sources. Encouraging greater use of renewable energy sources is a topical issue in all developed countries, and the reasons for this are numerous, ranging from economic ones to those relating to the reduction of the greenhouse effect. However, the precondition is the fundamental change in the consciousness of people. Man is an inseparable part of nature; any change or disturbance of balance in the nature directly affects not only the human life, but the existence of life on the Earth, in general.